Hip and knee proprioception in elite, amateur, and novice tennis players - Lin, Chien-Ho; Lien, Yu-Hui; Wang, Shwu-Fen; Tsauo, Jau-Yih (American journal of physical medicine & rehabilitation, 2006)
The purposes of this study were: (1) to show the differences of lower limb proprioception in three different groups of normal male subjects-elite, amateur, and novice tennis players-and between the skill-dominant and stance-dominant hip and knee and (2) to test the sensitivity of closed-chain reposition test in the three groups. There were 22, 20, and 20 subjects in the three groups, respectively. Proprioception was tested with the closed-chain reposition method. Absolute error and variable error were calculated. One-way analysis of variance and Tukey's test were used to test the differences. The proprioception of the hip joints of the elite players was significantly better than that of the other two groups in absolute error (P < 0.0167). In variable error analysis, the proprioception of the stance-dominant leg of the elite players was significantly better than that of the novice players (P < 0.0033). Findings of this study supported that the proprioception of elite players was the best. The closed-chain reposition test had good discriminating power between the elite players and the others.